Behavior of structural polymer-modified concrete containing recycled aggregates. Issue 8 (18th April 2017) - Assaad, Joseph; Daou, Yehia
Abstract: The use of recycled concrete aggregate (RCA) in structural applications is hindered by the inferior concrete mechanical performance and unpredictable behavior with embedded steel reinforcement. The main objective of this paper is to evaluate whether the addition of small amounts of styrene-butadiene rubber (SBR) polymeric latexes could mitigate the drop in RCA concrete properties. Two series of mixtures prepared with 320 or 440 kg/m 3 cement were tested by direct bond and beam-end methods; the SBR addition rates varied from 1 to 3% of cement mass. Test results showed that SBR could remarkably improve RCA concrete workability as well as compressive and splitting tensile strengths. The initial stiffness of load vs. slip curves was considerably accentuated, reflecting increased interfacial shear stresses between the reinforcing bar and surrounding concrete. Also, the responses of ascending curves showed extended nonlinear regions together with higher ultimate bond strengths at failure. The experimental direct bond and beam-end test data are compared with the design bond strengths determined by ACI 318-14, European Code EC-2, and fib Model Code MC2010.